Influenza virus detection: driving change in public health laboratories in the Western Pacific Region - Raynal C Squires; Patrick C Reading; Sheena G Sullivan; Ian G Barr; Frank Konings (World Health Organization Regional Office for the Western Pacific, 2019)
As we observe the 100th anniversary of the 1918 influenza pandemic, we are reminded of the importance of preparedness for and adequate response to influenza, and the critical role of influenza surveillance through laboratory detection. Influenza virus detection has helped drive the development of diagnostic and virology laboratories in the World Health Organization (WHO) Western Pacific Region over the last 10-15 years, at the same time strengthening their capacity to detect and respond to infectious threats beyond influenza. Such cross-cutting approaches are advocated under the Asia Pacific Strategy for Emerging Diseases and Public Health Emergencies (APSED III),1 which continues to guide Member States in advancing implementation of the International Health Regulations, 20052 and has a dedicated focus on strengthening laboratory capacities.